The Effect of Corporate Governance Mechanisms and Intellectual Capital on Financial Performance with Company Value as an Intervening Variable - Aprilia, Berliana; Pratiwi, Nila; Pondrinal, Muhammad (Universitas Mercu Buana, 2024)
This study aims to determine how much influence corporate governance mechanisms and intellectual capital have on financial performance with firm value as an intervening variable. In this study, the object used is a Banking Company listed on the Indonesia Stock Exchange (BEI) in 2018-2022. The data collection method is through secondary data and library research with data sourced from quantitative data. This study used 41 samples of banking companies with purposive sampling method through descriptive statistical analysis and multiple linear regression analysis. Based on the research results obtained from the Partial Test (t test) obtained: (a) The corporate governance mechanism has no significant effect on firm value. (b) Intellectual Capital has a significant effect on firm value. (c) Corporate governance mechanisms have no significant effect on financial performance. (d) Intellectual capital has a significant effect on financial performance. (e) Firm value has no significant effect on financial performance. (f) Corporate governance mechanisms have no significant effect on financial performance through firm value. (g) Intellectual capital has no significant effect on financial performance through firm value.